Penyuluhan Bahaya Rokok Elektrik Bagi Kesehatan Kepada Remaja Persaudaraan Setia Hati Terate Ranting Tugu Semarang - Lucky Restyanti Wahyu Utami; Aryadiva Nugrahaning Prayoga; Muhammad Fa'iq Rahmandinullah; Slamet Utomo; Rose Malinda Andamari Wahyu Utami; Hermien Nugraheni; Sukini Sukini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Electric cigarettes or what are often called vapes are a type of electronic nicotine delivery agent. In electric cigarettes what is inhaled does not come from dry tobacco leaves, but liquid. In some circles, it is said that electric cigarettes are considered safer than conventional cigarettes, apart from that, electric cigarettes are considered to be a technique for reducing smoking habits for users. The aim of the community service activities carried out for the teenagers of Persaudaraan Setia Hati Terate Ranting Tugu Semarang is to increase teenagers' knowledge of the dangers of electric cigarettes for health. Community service activities are carried out using the lecture method. Based on the community service activities that have been carried out, the results obtained are an increase in teenagers' knowledge of the dangers of electric cigarettes for health and the desire of teenagers who smoke to stop smoking.